Stereotactic Body Radiation Therapy for Patients with Heavily Pretreated Liver Metastases and Liver Tumors - Lanciano, Rachelle; Lamond, John; Yang, Jun; Feng, Jing; Arrigo, Steven; Good, Michael; Brady, Luther (Frontiers in Oncology, 2012)
We present our initial experience with CyberKnife stereotactic body radiation therapy (SBRT) in a heavily pretreated group of patients with liver metastases and primary liver tumors. From October 2007 to June 2009, 48 patients were treated at the Philadelphia CyberKnife Center for liver metastases or primary liver tumors. We report on 30 patients with 41 discrete lesions (1-4 tumors per patient) who received an ablative radiation dose (BED ≥ 79.2 Gy10 = 66 Gy EQD2). The treatment goal was to achieve a high SBRT dose to the liver tumor while sparing at least 700 cc of liver from radiation doses above 15 Gy. Twenty-three patients were treated with SBRT for metastatic cancer to the liver; the remainder (n=7) were primary liver tumors. Eighty-seven percent of patients had prior systemic chemotherapy with a median 24 months from diagnosis to SBRT; 37% had prior liver-directed therapy. Local control was assessed for 28 patients (39 tumors) with 4 months or more follow-up. At a median follow-up of 22 months (range, 10-40 months), 14/39 (36%) tumors had documented local failure. A decrease in local failure was found with higher doses of SBRT (p = 0.0237); 55% of tumors receiving a BED < 100 Gy10 (10/18) had local failure compared with 19% receiving a BED > 100 Gy10 (4/21). The two-year actuarial rate of local control for tumors treated with BED > 100 Gy10 was 75% compared to 38% for those patients treated with BED < 100 Gy10 (p = 0.04). At last follow-up, 22/30 patients (73%) had distant progression of disease. Overall, 7 patients remain alive with a median survival of 20 months from treatment and 57 months from diagnosis. To date, no patient experienced persistent or severe adverse effects. Despite the heavy pretreatment of these patients, SBRT was well tolerated with excellent local control rates when adequate doses (BED>100 Gy10) were used. Median survival was limited secondary to development of further metastatic disease in the majority of patients.